Urban planning effectiveness and citizen satisfaction. A systematic literature review. - Caicedo, Y. (2025)
Background The population is increasingly demanding a better quality of life in their territories, which requires better urban planning. This study aims to find out the effectiveness of urban planning implemented by local governments on citizen satisfaction. Method A systematic literature review was conducted exploring the evolution of the state-of-the-art databases in Scopus, WOS and Dimensions, involving a relevant selection of empirical studies on the effectiveness of urban planning on citizen satisfaction, using quality criteria and the application of the PRISMA diagram. Results The findings in the various empirical contributions find converging in three main blocks the contributions related to: (i) Urban planning as a catalyst for the impact of citizen satisfaction, given that using the planning tool will lead to the development of local policies based on the Neoliberalism approach for smart urban development; (ii) Theoretical contributions for urban planning that contextualises a modernist planning based on a multidimensional aspect to address quality of life for modern well-being and (iii) Smart planning for citizen satisfaction for the design and implementation of public governance reforms aimed at optimising urban planning management at the local level for smart urban city development. Conclusion There is strong theoretical and empirical support that is closely linked to sustainable development, happiness, public space, urban growth, urban areas, satisfied customers and urban residents. Future research should examine the relative weight of urban planning dimensions and effectiveness in the sustainable development of territories and citizen satisfaction.